Long-term biopermanence of ceramides, cholesteryl esters, and ether-linked triglycerides with very-long-chain PUFA in the cadmium-damaged testis - Zanetti, Samanta Romina (2014)
Cadmium is known to harm rat testis by causing the dose-dependent apoptotic or necrotic death of seminiferous epithelium cells. Here we investigated how this affects the lipids with long-chain (C18-C22) and very-long-chain (C24-C32) polyunsaturated fatty acids (VLCPUFA) typical of spermatogenic and Sertoli cells. A severe acute inflammatory reaction resulted from the massive necrotic death of these cells two days after a single high (4 mg/kg) dose of CdCl2. This led to the conversion of most testicular glycerophospholipids to diradylglycerols (DRG) and free fatty acids (FFA) and of most sphingomyelins to ceramides (Cer). By day 30 the testis weight had decreased three fold. The DRG and FFA had been metabolized but, unexpectedly, ceramides persisted. Also slow to disappear were VLCPUFA-containing triacylglycerols from former germ cells and ether-linked triglycerides and cholesteryl esters (CE) from former Sertoli cells. Similar results were observed 30 and 45 days after administering repeated small non proinflammatory CdCl2doses (1 mg/kg). At day 30 after both treatments, an amorphous material replaced the original seminiferous tubules and testicular macrophages populated the interstitium. Species of CE and etherlinked triglycerides containing fatty acids other than VLCPUFA steadily accumulated in the irreversibly damaged testis, a manifestation of the activity of phagocytic cells. The long-term permanence of original VLCPUFA-containing neutral lipids, especially ceramides, indicates that these cells were slow to clear out the acellular material contained in seminiferous tubules, pointing to a form of silent chronic inflammation as an additional outcome of the multifactorial commotion caused in the testis by experimentally administered cadmium.